IMPROVING THE ABILITY TO RECOGNIZE SYLLABLES USING THE MAHARAJA METHOD ASSISTED WITH FLASH CARD AND THE SNAKE AND LADDERS GAME IN BHINEKA KINDERGARTEN STUDENTS IN THE 2022/2023 ACADEMIC YEAR - Rose Ida, Farista (Journal of Teaching and Education, 2023)
The problem taken in this research is that students' ability to recognize and differentiate syllables is still low, so it needs to be improved using more effective strategic methods to stimulate students' enthusiasm and ability to recognize syllables. If we look at the learning method, it is felt that the Maharaja method is more appropriate to be applied in the activity of recognizing syllables in group B at Bhinneka Kindergarten because the children do not feel burdened with learning and do not separate their play activities. This type of research is classroom action research. Analysis of the research results shows that there was an increase in students' abilities in cycle 1, children's completion reached 58.3% and there was an increase in cycle II, increasing to 91.6% and only 1 student out of 12 students had not yet completed it. The use of the Maharaja method in this classroom action research based on student learning results was concluded to improve the ability to recognize syllables for Bhinneka Kindergarten students in Semarang.Â Â